Developing a tactical metric to estimate the defensive area of soccer teams: The defensive play area - Clemente, F. M.; Martins, F. M. L.; Couceiro, M. S.; Mendes, R. S.; Figueiredo, A. J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2016)
This study proposes a computational method to inspect the tactical position of players during the match and a new metric to analyse the defensive pressure made by a soccer team. These metrics only require Cartesian information about the players` positions on the field. As a case study, three matches played by the same professional soccer team were considered, including variables computed for the half of the match (first half vs second half) and the final score of the game for an analysis of variance of tactical performance, trying to identify the influence of such variables on the collective organisation. The data were collected at 1 Hz and from this process, 9218 instances of useful time were collected. The results revealed that the different kinds of final scores had significant effects on the tactical performance. The comparison between two halves of the match revealed significant differences with a small effect size on tactical performance. In summary, this study showed that these new tactical metrics can be a computational option to increase a coaches` knowledge about the defensive organisation of soccer teams, giving them the possibility to augment their own perception with metrics that can provide specific information.